2014
DOI: 10.1016/j.ejca.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Secretogranin II is overexpressed in advanced prostate cancer and promotes the neuroendocrine differentiation of prostate cancer cells

Abstract: The present data show that SgII is highly expressed in advanced PCa and may contribute to the neuroendocrine differentiation by promoting the formation of secretory granules and the proliferation of PCa cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…CAV2 was a major component of the inner surface of caveolae, and the expression of CAV2 was necessary for the control of E2-dependent cellular proliferation in breast cancer (Totta et al, 2016). SCG2 was a member of the chromogranin/secretogranin family of neuroendocrine secretory proteins, and it might contribute to the neuroendocrine differentiation by promoting the formation of secretory granules and the proliferation of prostate cancer cells (Courel et al, 2014). The SLC6A1 gene encoded a gamma-aminobutyric acid (GABA) transporter, which removes GABA from the synaptic cleft (Hirunsatit et al, 2009), but there have been no studies in relation to cancer as of now.…”
Section: Discussionmentioning
confidence: 99%
“…CAV2 was a major component of the inner surface of caveolae, and the expression of CAV2 was necessary for the control of E2-dependent cellular proliferation in breast cancer (Totta et al, 2016). SCG2 was a member of the chromogranin/secretogranin family of neuroendocrine secretory proteins, and it might contribute to the neuroendocrine differentiation by promoting the formation of secretory granules and the proliferation of prostate cancer cells (Courel et al, 2014). The SLC6A1 gene encoded a gamma-aminobutyric acid (GABA) transporter, which removes GABA from the synaptic cleft (Hirunsatit et al, 2009), but there have been no studies in relation to cancer as of now.…”
Section: Discussionmentioning
confidence: 99%
“…3.5 | Immunohistochemistry and effects of IL-6 on the expression of SCG2 protein and mRNA (Berard, Severini, & Coombs, 2015;Courel et al, 2014). To verify the results of screening DEGs in transcriptome sequencing, we first assessed SCG2 immunoreactivity in cancer and paracancerous tissues.…”
Section: Il-6 Expression Was Upregulated In Facamentioning
confidence: 99%
“…Clinically, it has been shown that EM66 is present in tumoural chromaffin cells and represents a sensitive diagnostic and pronostic marker of pheochromocytoma . Furthermore, EM66 and its precursor SgII are highly expressed in advanced prostate adenocarcinoma and may contribute to the neuroendocrine differentiation of prostate cancer cells by promoting the formation of secretory granules and the proliferation of tumoural cells …”
Section: Introductionmentioning
confidence: 99%
“…19 Furthermore, EM66 and its precursor SgII are highly expressed in advanced prostate adenocarcinoma and may contribute to the neuroendocrine differentiation of prostate cancer cells by promoting the formation of secretory granules and the proliferation of tumoural cells. 20 Neuroanatomical studies have revealed that, in the jerboa, EM66producing neurones are present in various hypothalamic structures, including the suprachiasmatic, supraoptic, parvocellular paraventricular (pPVN) and arcuate (ARC) nuclei, and the lateral hypothalamic area (LHA). 18 Similarly, in the rat hypothalamus, EM66-containing neurones are found in the pPVN, preoptic area, ARC and in the LHA.…”
Section: Introductionmentioning
confidence: 99%